Pengawasan Ombudsman Republik Indonesia Perwakilan Jawa Tengah terkait maladministrasi pelayanan publik. Studi Kasus Pungutan Liar Program Nasional Agraria Tahun 2017 - Achmad Nur Fuad; Dewi Erowati (Journal of Politic and Government Studies, 2019)
A land certificate is an important document that shows proof of someone's ownership and rights to land. The complete systematic land registration program offers to people to make land certificates at a low cost. However, in its implementation there were many problems and irregularities encountered, especially the high collection of costs to the community. In 2017, Kudus Regency became one of the cities with the largest Prona certificate quota and there were often many problems in the implementation of Prona. Ombudsman Republik Indonesia is present as an institution that functions to oversee and resolve public service problems that occur in the community. Ombudsman Republik Indonesia Perwakilan Jawa Tengah as the representative of the central Ombudsman supervised and tries to resolve the problems that occurred during the implementation of Prona in Kudus Regency. This study uses qualitative research methods with a case study approach. The purpose  of using this method is to dig up data and information accurately and specifically, so that the data and information produced is complete and in-depth. Data collection techniques used were interviews with eight informants, literature review and review of documents relating to the supervision of the Ombudsman Republik Indonesia.The results of this study indicate that the supervision carried out by Ombudsman Republik Indonesia Perwakilan Jawa Tengah in supervising Prona in Kudus Regency was in accordance with its functions, duties, and authority. Supervision carried out by the Ombudsman Republik Indonesia Perwakilan Jawa Tengah is to conduct an investigation of its own initiative, conduct preventive supervision and cooperate with other law enforcement agencies. Ombudsman Republik Indonesia Perwakilan Jawa Tengah tries to resolve the Prona problem reported by the public and Ombudsman Republik Indonesia Perwakilan Jawa Tengah also sent suggestions for improvements to stakeholders to prevent problems from recurring. The thing that was lacking in the supervision was Ombudsman Republik Indonesia Perwakilan Jawa Tengah did not involve the community in supervising Prona in Kudus Regency. Keywords: Supervision, Prona, Ombudsman Republik Indonesia Perwakilan Jawa Tengah